Between syntax and semantics [ - Huang, Cheng-Teh James (Routledge leading linguists, 2010)
Contains articles that represent the best of the author's work on the syntax-semantics interface. This title includes three general topics such as: questions, indefinites and quantification; anaphora; as well as, lexical structure and the syntax of events